الوظيفة المالية في المؤسسة الاقتصادية دراسة حالة مؤسسة سوف للدقيق - صفاء, سعدان; رونق, مرابط; آمة, جلالي; انتصار, مأمون (جامعة الوادي - University of Eloued, 2023)
"هدفت هذه الدراسة إلى تحليل مصادر التمويل بمؤسسة الدقيق سوف، وذلك من خالل التطرق إلى املصادرالداخليةوالخارجية للمؤسسة وهذا اعتمادا على امليزانيات املالية للسنوات 2021/2020/2019 ولقد توصلت الدراسة إلى أن شركة سوف للدقيق تحتوي على مصادر داخلية تتكو ن من التمويل الذاتي واملساهمات واالحتياطات وأخرى خارجيةمتمثلةفي افتراضات من البنوك واألسهم في البورصات، أما في جانب استخدامات املؤسسةفلديها استخدامات دائمة كالتثبيتات العينية واملعنوية وتثبيتات مالية كسندات املساهمة وأخرى غير دائمة متمثلة في املخزونات واملواد األولية تامة الصنع، ومنه يمكن القول أن املؤسسة تمتلك جدارة ائتمانية تمكنهامن زيادةالتوسع في الاستثمارو الاقتراض . " "This study aimed to analyze the funding sources of the Souf Flour Corporation, by addressing the internal and external sources of the corporation, depending on the financial budgets for the years 2019/2020/2021. The study concluded that the Souf Flour Company contains internal sources consisting of self-financing, contributions, reserves, and others. External ones represented in assumptions from banks and stocks in the stock exchanges. As for the uses of the institution, it has permanent uses such as in-kind and moral fixations, financial fixations such as contribution bonds, and other non-permanent ones represented in stocks and finished raw materials, and from it it can be said that the institution has creditworthiness that enables it to increase the expansion of investment. and borrow. "
Keywords: الوظيفة المالية. مصادر التمويل. شركة سوف للدقيق; financial. Function, funding source, souf flour Company